On InSAR ambiguity resolution for deformation monitoring - Teunissen, Peter (Versita, 2006)
Integer carrier phase ambiguity resolution is the key to fast and high-precision satellite positioning and navigation. It applies to a great variety of current and future models of GPS, modernized GPS and Galileo. It also applies to stacked radar interferometry for deformation monitoring, see e.g. [Hanssen, et al., 2001]. In this contribution we apply the integer least-squares' principle to the rank defect model of stacked InSAR carrier phase data. We discuss two ways of dealing with the rank defect for ambiguity resolution. One is based on the use of a priori data, the other is based on the use of an interval constraint on the deformation rate.